Penguatan Literasi dan Keterampilan Menulis Melalui Program “Bergerak Membangun Skill Kelas Writing” Komunitas Bergerak Berdampak Batch 2 - Badi'ah, Roudlotul; Al-Mashuri, A'lie Ilham; Syauqi, Ahmad; Mu'ah, Mu'ah; Wiratama, Dadang; Dedyansyah, Achmad Farid; Effendi, Rusfian (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to enhance writing skills through community-based training and mentoring, with the goal of strengthening the soft skills of outstanding youth and contributing to transformative efforts within Indonesia’s education system. The methods applied in this program include Community-Based Participatory Research (CBPR) and Participatory Learning and Action (PLA). The evaluation instrument consisted of questionnaires analyzed using descriptive quantitative and qualitative approaches. The results of this program demonstrated significant benefits. Participants in the writing class expressed high appreciation for both the learning materials and the mentors’ attitudes, scoring 9 out of 10, while the level of interactivity reached a perfect score of 10. Mentor feedback also contributed to the success of participants, one of whom achieved recognition in the Top 30 National Essay Competition. This activity successfully improved participants’ writing soft skills and played a role in fostering excellent young individuals, indicating that education can indeed be transformed through collaborative and participatory efforts.